2017
DOI: 10.1371/journal.pone.0174139
|View full text |Cite
|
Sign up to set email alerts
|

Violent relationships at the social-ecological level: A multi-mediation model to predict adolescent victimization by peers, bullying and depression in early and late adolescence

Abstract: BackgroundFrom the social-ecological perspective, exposure to violence at the different developmental levels is fundamental to explain the dynamics of violence and victimization in educational centers. The following study aims at analyzing how these relationships are produced in the Peruvian context, where structural violence situations exist.MethodsA multi-mediation structural model with 21,416 Peruvian adolescents (M = 13.69; SD = 0.71) was conducted to determine the influence of violence in the school envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 60 publications
2
37
1
9
Order By: Relevance
“…At the micro‐level analysis, as proposed in the fourth hypothesis, it has been confirmed that a disruptive school environment (based on violence) increases the possibilities of adults harassing students and the appearance of negative bystanders and aggressive behaviors in students. These results are similar to recent data from Peruvian schools that show a clear relationship between disruptive school environments and the aggressiveness exhibited by teachers (Oriol et al ., ). Nevertheless, it must be noted that this study addresses adults in schools and not teachers alone.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At the micro‐level analysis, as proposed in the fourth hypothesis, it has been confirmed that a disruptive school environment (based on violence) increases the possibilities of adults harassing students and the appearance of negative bystanders and aggressive behaviors in students. These results are similar to recent data from Peruvian schools that show a clear relationship between disruptive school environments and the aggressiveness exhibited by teachers (Oriol et al ., ). Nevertheless, it must be noted that this study addresses adults in schools and not teachers alone.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental factors such as the reaction of staff to cases of bullying and the awareness of school about these issues have a direct influence on violence prevention (Bradshaw, Waasdorp, O'Brennan & Gulemetova, ; Wienke‐Tortura, MacKinnon‐Lewis, Ellis et al ., ). Similarly, a recent study revealed that violent school environments influence the aggressiveness that teachers exhibit toward students, consequently favoring peer victimization (Oriol, Miranda, Amutio, Acosta, Mendoza & Torres‐Vallejos, ). Teacher‐student relationships: one of the indicators that might fuel or reduce violence is the relationship between teachers and students (Saarento, Kärnä, Hodges & Salmivalli, ). Teachers’ beliefs influence the occurrence of bullying dynamics in the classroom (Troop‐Gordon & Ladd, ), and the support offered to students by the school may also be an important moderating variable in cases of domestic violence (Wang, Brinkworth & Eccles, ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Por otra parte, los resultados de la validez del cuestionario señalan que el diagnóstico brindado se asocia de forma significativa con los trastornos del dormir y un estado de ánimo deprimido. Esto es consistente con los resultados a las investigaciones que señalan una relación entre la victimización escolar con problemas de salud mental (Hunter et al, 2014;Klomek et al, 2013;Kubiszewski et al, 2014;Oriol et al, 2017;Wolke y Lereya, 2014). De la misma forma, los resultados señalaron una asociación negativa entre el diagnóstico brindado por el cuestionario y la satisfacción que tuvieron los participantes en la escuela y con su desempeño escolar.…”
Section: Discussionunclassified
“…Por ejemplo, existe evidencia que asocia la victimización escolar por pares con los problemas para dormir, demostrando que tanto quienes sufren de victimización como quienes la realizan, tienen patrones de sueño diferentes de aquellos quienes no sufren o realizan victimización (Hunter, Durkin, Boyle, Booth, y Rasmussen, 2014;Kubiszewski, Fontaine, Potard, y Gimenes, 2014), tienen una peor calidad del sueño (Zhou et al, 2015), y las víctimas muestran un mayor riesgo a presentar pesadillas y terrores nocturnos (Wolke y Lereya, 2014). De igual forma se ha asociado la victimización escolar con posteriores problemas como la depresión y el suicidio (Klomek et al, 2013;Oriol et al, 2017), y se considera importante evaluar la depresión y la victimización como un factor de riesgo para el suicidio (Kodish et al, 2016). En general, los resultados de éstas investigaciones señalan que aquellos que sufren victimización tienen un mayor riesgo de presentar depresión debido a malas estrategias de afrontamiento (Undheim, Wallander, y Sund, 2016), e incluso tienen mayores probabilidades de presentar depresión clínica en la vida adulta (Bowes, Joinson, Wolke, y Lewis, 2015).…”
Section: Introductionunclassified